Chlorophyll a fluorescence transient and vegetative growth in conilon coffee under different nitrogen sources - Oliosi, Gleison; Rodrigues, José de Oliveira; Falqueto, Antelmo Ralph; Pires, Fábio Ribeiro; Monte, José Antônio; Partelli, Fábio Luiz (Coffee Science - ISSN 1984-3909, 2017)
The use of nitrogen fertilizers is an effective resource to increase the coffee yield, so that the improvement and /or generation of new techniques that assist in the management of nitrogen fertilization are essential, as will contribute to increase nitrogen use efficiency (N). Thus, this study aimed to determine the chlorophyll a fluorescence transient and vegetative growth in Conilon coffee under different nitrogen sources. The experiment was carried out in Nova Venécia - ES - Brazil, on coffee plantation Conilon cultivar “Vitória Incaper 8142”. Were evaluated five sources of nitrogen fertilizers: urea common, urea + NBPT, urea + Cu and B, urea + S, and ammonia nitrate. The chlorophyll a fluorescence maximum did not differ in any of the times examined. The values of relative chlorophyll index (RCI) alternated their significance with respect to treatments throughout the evaluation dates. The N sources were not responsible, singly, with changes to the RCI. The sources of nitrogen fertilizers with increased efficiency exhibited low influence on transient fluorescence of chlorophyll a and do not influence the vegetative growth of the coffee.